Late postoperative opacification of a hydrophilic–hydrophobic acrylic intraocular lens. Issue 9 (September 2016) - Bompastor‐Ramos, Paula; Póvoa, João; Lobo, Conceição; Rodriguez, Alejandra E.; Alió, Jorge L.; Werner, Liliana; Murta, Joaquim N.
Abstract : Purpose : To report late postoperative opacification of a model of hydrophilic–hydrophobic acrylic intraocular lens (IOL) as well as the clinical consequences and laboratory characteristics. Setting : Department of Ophthalmology, Centro Hospitalar e Universitário de Coimbra, Coimbra, Portugal. Design : Retrospective case series. Methods : Medical records were reviewed of patients with Lentis LS‐502‐1 IOL opacification reporting visual loss who had IOL explantation between November 2013 and March 2015. Patients were identified in the emergency room or during regular follow‐up visits. Explanted IOLs were analyzed at the Ophthalmic Explants Biobank, Vissum, Spain, or at the John A. Moran Eye Center, University of Utah, USA. Results : Twenty opacified IOLs were explanted from 19 patients. The mean interval between cataract surgery and diagnosis of opacification was 29.15 months ± 9.57 (SD) (range 6 to 45 months). Opacification led to a statistically significant reduction in corrected distance visual acuity (mean 0.86 ± 0.76 logMAR; P < .001) and occurred in 5.1% of the hydrophilic–hydrophobic acrylic IOLs implanted at the department. The most frequently associated medical conditions were arterial hypertension, diabetes, and glaucoma. All IOLs but 1 had a similar pattern of opacification, with yellowish diffuse opacification uniformly distributed and calcium deposits on the surface and/or subsurface of the optic and haptics and within the IOL material. Conclusions : Opacification of the hydrophilic–hydrophobic acrylic IOL was found in a significant number of patients and had a significant effect on their vision. The opacification was attributed to primary calcification. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.